A questão racial pensada entre o “método científico” e a paixão : um estudo comparado entre José Ingenieros e Manoel Bomfim-Argentina e Brasil (1900-1920) - Neiva, Ruth Cavalcante (2015)
This paper aims to make a comparative analysis of how the thematic of Race was discussed by the Italian-Argentinian José Ingenieros and by the Brazilian Manoel Bomfim in the first two decades of the twentieth century. The hypothesis of this work is that both authors seek to define what would be the “legitimate folk” of their respective nations based on a racial bias. This research is divided into three parts: The first chapter seeks to delineate the intellectual profile of Ingenieros and Bomfim so that the reader can visualize the professional trajectory of these men and have a better understanding of them; The second chapter demonstrates the conceptions of world in which the authors were raised and how they echoed in their writings; and the last chapter is dedicated to the analysis of the fonts Sociologia Argentina by Ingenieros, and América Latina: males de origem by Bomfim, in a way that makes it possible to reflect on how these intellectuals thought the race issue and how they related it to their conceptions of “ideal folk” in their respective nations.